Ultrasound-assisted lipase catalyzed hydrolysis of aspirin methyl ester - Chiplunkar, Pranali P. (2018)
The ultrasound-assisted hydrolysis of aspirin methyl ester (AME) was investigated using immobilized Candida antarctica lipase B (CALB) (1%) in the presence of solvents like triolein, chloroform (CHCl3) and dichloromethane (DCM). The effect of ultrasound and the role of water on the conversion rates have also been investigated. Proton nuclear magnetic resonance spectroscopic (1H NMR) was chosen to calculate hydrolysis convertion rates. We observed that lipase-ultrasound assisted hydrolysis of AME in the presence of triolein and water showed the highest hydrolysis conversion rate (65.3%). Herein low water amount played an important role as a nucleophile being crucial for the hydrolysis yields obtained. Lipase activity was affected by the conjugated action of ultrasound and solvents (35.75% of decrease), however not disturbing its hydrolytic efficiency. It was demonstrated that lipase is able to hydrolyse AME to methyl 2-hydroxy benzoate (methyl salicylate), which applications include fragrance agents in food, beverages and cosmetics, or analgesic agent in liniments.